Alliance building and eventful protests: comparing Spanish and Portuguese trajectories under the Great Recession. (4th March 2022) - Portos, Martín; Carvalho, Tiago
ABSTRACT: Social movement research has shed light on the relationship between processes of alliance building and multiple factors related to political opportunities, framing, identities, networks and resource mobilization. However, less is known about the impact of eventful protests on coalition building dynamics. Drawing on a paired comparison between the Portuguese and Spanish cycles of protest under the Great Recession, we aim at accounting for social movement alliances over time. While these countries present parallel protest dynamics until 2011, after that point two eventful protests lead each country into different trajectories. While the cycle in Portugal was marked by intermittent large protest events dominated by institutional actors, in Spain the peak of mobilization was consistently high between 2011 and 2013. When comparing these cases two factors stand out: the mobilization capacity and the autonomy of new emerging actors vis-à-vis institutional ones. Eventful protests were a key factor in articulating these elements. In Spain, the strength and autonomy of 15M assemblies and anti-austerity actors facilitated the formation of strategic alliances with trade unions. In Portugal, transversal initiatives and sustained alliances did not follow after the Geração à Rasca events. These emerged only later in the cycle, however were nonetheless hampered by overlapping membership and a lack of autonomy from institutional actors. Two original protest event analysis datasets are used to illustrate these arguments.